Possibilities of application of incremental sheet-forming technique in aircraft industry - Trzepieciński, Tomasz; Krasowski, Bogdan; Kubit, Andrzej; Wydrzyński, Dawid (Advances in Mechanical and Materials Engineering, 2018)
The article includes the characteristics of incremental forming of the sheet using the following two methods: Single Point Incremental Forming and Two Point Incremental Forming. The factors influencing the possibility of method application and the phenomena that limit the use of incremental forming of the sheet are presented. Based on the conducted experimental test, the disadvantages and advantages of single point incremental forming are specified. Possibilities for the use of the presented incremental forming technique for manufacturing elements in the aircraft industry are also included.